A Systematic Review of the Benefits and Risks of Anticoagulation Following Traumatic Brain Injury. Issue 4 (July 2015) - Shen, Xian; Dutcher, Sarah K.; Palmer, Jacqueline; Liu, Xinggang; Kiptanui, Zippora; Khokhar, Bilal; Al-Jawadi, Mohammad H.; Zhu, Yue; Zuckerman, Ilene H.
Abstract : Objective: To synthesize the existing literature on benefits and risks of anticoagulant use after traumatic brain injury (TBI). Design: Systematic review. A literature search was performed in MEDLINE, International Pharmaceutical Abstracts, Health Star, and CINAHL (Cumulative Index to Nursing and Allied Health Literature) on October 11, 2012, and updated on September 2, 2013, using terms related to TBI and anticoagulants. Main Measures: Human studies evaluating the effects of post-TBI anticoagulation on venous thromboembolism, hemorrhage, mortality, or coagulation parameters with original analyses were eligible for the review. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guideline was followed throughout the conduct of the review. Results: Thirty-nine eligible studies were identified from the literature, of which 23 studies with complete information on post-TBI anticoagulant use and patient outcomes were summarized in this review. Meta-analysis was unwarranted because of varying methodological design and quality of the studies. Twenty-one studies focused on the effects of pharmacological thromboprophylaxis (PTP) post-TBI on venous thromboembolism and/or progression of intracranial hemorrhage, whereas 2 randomized controlled trials analyzed coagulation parameters as the result of anticoagulation. Conclusion: Pharmacological thromboprophylaxis appears to be safe among TBI patients with stabilized hemorrhagic patterns. More evidence is needed regarding effectiveness of PTP in preventing venous thromboembolism as well as preferred agent, dose, and timing for PTP. Abstract : Supplemental Digital Content is Available in the Text.